Hubungan Produk,Merek,Dan Promosi Terhadap Keputusan Pembelian Sepeda Motor Yamaha Mio M3 Di PT Thamrin Brother Argamakmur - sudriyanti putri; Edwarman Edwarman (STIA Bengkulu, 2023)
The aim of the study was to determine the relationship between product, brand and promotion on purchasing decisions for Yamaha Mio M3 motorbikes in Bengkulu City. The analytical method used is Spearman Rank Correlation analysis. The results of the Spearman rank test show that there is a strong relationship between the product and the decision to purchase a Yamaha Mio M3 motorbike at PT Thamrin Brother Argamakmur with a correlation value of 0.646. For the relationship between the brand and the purchasing decision, there is a correlation value of 0.707 with strong assessment criteria. The results of the spearman rank test show that there is a very strong relationship between promotion and the decision to purchase a Yamaha Mio M3 motorbike at PT Thamrin Brother Argamakmur with a correlation value of 0.815. The results of testing the product relationship hypothesis on purchasing decisions show that the tcount is greater than ttable (5.483> 1.681). Means that between products have a positive and significant relationship to purchasing decisions. The results of the hypothesis test of brand relations on purchasing decisions of Honda Beat motorbikes show that the tcount is greater than ttable (6.480> 1.681). Means that the brand and purchasing decisions have a positive and significant relationship. The results of testing the hypothesis about the relationship between promotion and purchasing decisions show that the tcount is greater than ttable (9.112> 1.681). So between products have a positive and significant relationship to the decision to purchase a Yamaha Mio M3 motorbike at PT Thamrin Brother Argamakmur